2016
DOI: 10.1177/2380084416673798
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of a Cognitive Behavioral Therapy Resource for Children’s Dental Anxiety

Abstract: Cognitive Behavioral Therapy (CBT) is an evidence-based treatment for dental anxiety; however, access to therapy is limited. The current study aimed to develop a self-help CBT resource for reducing dental anxiety in children, and to assess the feasibility of conducting a trial to evaluate the treatment efficacy and cost-effectiveness of such an intervention. A mixed methods design was employed. Within phase 1, a qualitative "person-based" approach informed the development of the self-help CBT resource. This al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…The research aimed to evaluate the feasibility and preliminary effectiveness of a cognitive behaviour therapy (CBT)‐based guided self‐help intervention designed to reduce dental anxiety. Details of how this sample were recruited to the research and the how the CBT intervention was developed and delivered have been published elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…The research aimed to evaluate the feasibility and preliminary effectiveness of a cognitive behaviour therapy (CBT)‐based guided self‐help intervention designed to reduce dental anxiety. Details of how this sample were recruited to the research and the how the CBT intervention was developed and delivered have been published elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, after the therapy is finished, 91% of the subjects show no dental anxiety, as rated using various diagnostic criteria, which proves that it is highly effective [25]. The effectiveness of computer-based cognitive-behavioural therapy in reducing dental anxiety (as measured with MDAS) has been confirmed for patients aged 9-16 and 18-70 [6,26]. Another study has shown that four therapeutic sessions using cognitive restructuring are sufficient to significantly decrease dental anxiety levels in patients suffering from the condition [27].…”
Section: Basic Behavioural Methodsmentioning
confidence: 80%
“…Two respondents (9%) identified as being from a Black and Minority Ethnic group and ten (45%) were from the two most deprived quintiles according to the Index of Multiple Deprivation. Table 1 provides further summary details of the respondents' profile compared to those included in the original CBT study 14 , to illustrate that they were a representative sample. It can be seen that this follow up subgroup had similar mean self-report anxiety scores (MCDAS) to those found for the original study participants as a whole.…”
Section: Participants' Characteristicsmentioning
confidence: 99%
“…As so little is known of how children, who have received an intervention for their dental anxiety, fare in the longer term, the authors of the current paper contacted the participants of their original CBT study, one-year after discharge from the dental hospital service. 14 This was part of an ongoing CBT service development and evaluation. The specific objectives of this follow up inquiry were to explore children's self-reported levels of dental anxiety, attendance patterns and treatment experiences in general dental practice following a previous CBT intervention.…”
Section: Objectivementioning
confidence: 99%
See 1 more Smart Citation